Care management and nursing governance in a maternity ward: grounded theory - Fernanda Hannah da Silva Copelli; Roberta Juliane Tono de Oliveira; José Luís Guedes dos Santos; Aline Lima Pestana Magalhães; Vitória Regina Petters Gregório; Alacoque Lorenzini Erdmann
ABSTRACT Etjective: To understand the care management strategies used by nurses in the governance of nursing practice in a maternity ward. Method: Qualitative study based on grounded theory conducted with 27 participants, partitioned into four sample groups. The data were collected through semi-structured interviews and analyzed through open, axial, and selective coding. Result: The care management strategies used by the nurses were: planning professional practice, leading the nursing team, search for scientific knowledge, and training inthe best practices in obstetric care. Conclusion: Associating care management with nursing governance can foster better care outcomes and strengthen nursing autonomy when coordinating nursing work in maternity wards.